Guideline on the peri‐operative management of patients with sickle cell disease: Guideline from the Association of Anaesthetists. (3rd February 2021) - Walker, I.; Trompeter, S.; Howard, J.; Williams, A.; Bell, R.; Bingham, R.; Bankes, M.; Vercueil, A.; Dalay, S.; Whitaker, D.; Elton, C.
Summary: Sickle cell disease is a multisystem disease characterised by chronic haemolytic anaemia, painful vaso‐occlusive crises and acute and chronic end‐organ damage. It is one of the most common serious inherited single gene conditions worldwide and has a major impact on the health of affected individuals. Peri‐operative complications are higher in patients with sickle cell disease compared with the general population and may be sickle or non‐sickle‐related. Complications may be reduced by meticulous peri‐operative care and transfusion, but unnecessary transfusion should be avoided, particularly to reduce the risk of allo‐immunisation. Planned surgery and anaesthesia for patients with sickle cell disease should ideally be undertaken in centres with experience in caring for these patients. In an emergency, advice should be sought from specialists with experience in sickle cell disease through the haemoglobinopathy network arrangements. Emerging data suggest that patients with sickle cell disease are at increased risk of COVID‐19 infection but may have a relatively mild clinical course. Outcomes are determined by pre‐existing comorbidities, as for the general population.